Fusion of the L5-S1 Segment in Degenerative Lumbar Spine Disease Using the Extreme Lateral Interbody Fusion Technique: A Case Report Study - Schmid, Samuel Luca; Krappel, Ferdinand Anton; Marmentini, Saverio (Archives of Clinical and Medical Case Reports, 2019)
Study design: This study is a single center case report study with 3 cases of degenerative lumbar spine disease treated with the XLIF procedure at the level L5-S1. Objective: The purpose of this case report study is to demonstrate the possibility of treating degenerative lumbar spine disease at the level L5-S1 using the XLIF procedure. Summary and Background of Data: There are several standard surgical techniques for the treatment of degenerative lumbar spine diseases that have failed conservative treatment. Interbody fusion can restore the proper alignment of the spine hereby leading to indirect decompression of the nerve roots. The XLIF procedure is a relatively recent retroperitoneal and transpsoas major muscle approach allowing the insertion of interbody implants. This approach has shown good results but for anatomical reasons it is limited at the lumbar spine to the segments L1-L5. Methods: A single center case report study with 3 cases of degenerative lumbar spine disease treated with the XLIF procedure at the level L5-S1. Results: All 3 patient were successfully operated at the level L5-S1 with an XLIF procedure. Conclusion: This case series suggests that the XLIF procedure is a safe, feasible and timesaving procedure to treat the segment L5-S1 in selected patients with severe degenerative lumbar spine disease and failed conservative treatment. Preoperative anatomical evaluation of the correlation of the iliac crest to L5 is necessary. The procedure should be performed with the aid of neuromonitoring and direct visualization during dissection of the psoas muscle should be achieved.